2018
DOI: 10.1097/jom.0000000000001287
|View full text |Cite
|
Sign up to set email alerts
|

Effort–Reward Imbalance, Work–Privacy Conflict, and Burnout Among Hospital Employees

Abstract: Interventions aiming at increasing the compatibility of work and private life may substantially help to decrease burnout risk of professionals working in a health care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 28 publications
(59 reference statements)
4
33
0
8
Order By: Relevance
“…Nahezu alle Studien wei sen auf Zusammenhänge zwischen dem Vorliegen beruflichen Gra tifikationskrisen und Indikatoren psychischer und/oder körperlicher Gesundheit hin, z. B. für Depression [15], Burn-out [16], koronare Herzkrankheiten [17] oder Diabetes mellitus [18].…”
Section: Introductionunclassified
“…Nahezu alle Studien wei sen auf Zusammenhänge zwischen dem Vorliegen beruflichen Gra tifikationskrisen und Indikatoren psychischer und/oder körperlicher Gesundheit hin, z. B. für Depression [15], Burn-out [16], koronare Herzkrankheiten [17] oder Diabetes mellitus [18].…”
Section: Introductionunclassified
“…The effects seem to spill over into the postpartum period. In another a previous study among hospital employees in Switzerland, both concepts were found to be signi cantly associated with burnout, but WPC was found to be a stronger predictor for burnout than ERI among health professionals (73). Interestingly, when looking at hospital staff with different levels of professional education, ERI has been found to be more relevant for burnout in tertiary-educated staff.…”
Section: Psychosocial Work Stress-work-privacy Con Ict and Effortrewamentioning
confidence: 73%
“…Interestingly, when looking at hospital staff with different levels of professional education, ERI has been found to be more relevant for burnout in tertiary-educated staff. This indicates that in higher educated, professional groups such as therapists, physicians, and medical-technical staff effort-reward imbalance seems to be important for mental health (73). This could be due to a different perspective on the job such as a higher personal commitment and will to work after hours.…”
Section: Psychosocial Work Stress-work-privacy Con Ict and Effortrewamentioning
confidence: 99%
“…One factor that often leads to health professionals leaving their profession prematurely is work-related stress [2,3]. Health professionals affected by high levels of stress at work are more likely to suffer from burnout-symptoms, musculoskeletal disorders, coronary artery disease or poor sleep quality [4][5][6]. Moreover, stress at work can also negatively affect health professionals' job satisfaction and safety at work [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Incompatibility between work and private life (work-private life conflict) has been identified in previous studies as an important predictor for burnout, job dissatisfaction and lack of organisational commitment among health professionals [6,12,13]. An incompatibility between work and private life is described as a 'conflict a person may experience between the work role and other life roles' [14].…”
Section: Introductionmentioning
confidence: 99%